Connective tissue origin of the amyloid-related protein SAA (The Rockefeller University Press, 1976)
Protein SAA is a serum protein related to the major constituent of secondary amyloid fibrils, protein AA, and has been suggested to be a precursor of the amyloid protein AA. In the present study, the origin of SAA was investigated by studying human fetal tissues and cultured human fetal fibroblasts with the indirect immunofluorescence technique. Anti-SAA antibodies reacted strongly with cultured fibroblasts producing a fine fibrillary cytoplasmic staining and with extracellular fibrils in loose connective tissues and vessel walls. The reactions were specifically inhibited by absorption with degraded amyloid material, isolated protein AA, isolated protein SAA, and sera from patients with elevated levels of SAA. In contrast, no inhibition was seen with amyloid fibril material devoid of AA protein or by human sera in which SAA was not detectable by double-diffusion tests. These observations showed that SAA-like material is produced by fibroblasts and indicate that it is a normal constituent of developing extracellular connective tissue fibers.